(3GdJCUjd GdGSdGej dadSaI GdHUQjGJ (B/s - (3,YHjQ MSfjf Ydj GHQGgje s; (3GdSjO QRb GdMLQs; (3eLOj YeQs (2024)
(3hJTed gPg GdQSGdI GdYde GdHUQj GdCUdj aj GdMVGQI GdESdGejI cLRA ef GdJWhQ GdYdej, eY JSdjW GdVhA Ydi OhQ GdYdeGA hGdadGSaI GdRLGL GdPjf GSJdgehG ef GdbQBf GdPj jTLY Ydi GSJcTGa Gdchf(B. (3aj YUQfG GdMOjK, MjK ojYRi GdJbOe GdYdej ZGdkHG Edi GdMVGQI GdZQHjI, hjXgQ Cfg dG CUd EQLGY adSaI GdHUQjGJ hEOQGc GdHUQ Edi GdMVGQI GdESdGejI(B. (3fGbTJ GdQSGdI fThA Yde GdHUQjGJ YHQ eNJda GdMVGQGJ, eY GdJQcjR Ydi LghO GdYdeGA GdeHOYjf aj JQLeI hOQGSI GdfXQjGJ GdHUQjI(B. (3GSJNOeJ GdQSGdI efgkLG JLQjHkjG dEKHGJ GdfJGFL, eY GdGSJTgGO HBjGJ bQBfjI UYHI HGdfhQ hGdXd, ceUOQ ddEdgGe(B. (3Ufa GdQSGdI LghO GdYdeGA Edi KdGK eQGMd(B: (3ChdgG, JQLeI GdJQGK GdjhfGfj hJUMjM GdCSHGH GdYdejI; KGfjgG, JhMjO fXQjGJ HUQjGJ HhGSWI GHf GdgjKe; hKGdKgG, JUMjM Yde GdHUQjGJ ef GdYdeGA GdeSdejf(B. (3CNPJ fJGFL GdMVGQI GdESdGejI aj JGKjQ Yde GdHUQjGJ s
This thesis examines the origin of optics in Islamic civilization as a part of scientific development, highlighting the role of Muslim scholars and philosophers inspired by the Quran, which encourages the exploration of the universe. In our modern era, where scientific advancement is often attributed to Western civilization, it becomes essential to trace the foundations of the philosophy of optics and visual perception back to Islamic civilization. This necessity arises from the limited revival of scientific heritage on one hand and the lack of knowledge regarding the efforts of ancestors on the other. The thesis discusses the emergence of optics across various civilizations, focusing on the contributions of Muslim scholars in translating and studying optical theories. It employs an experimental methodology to validate results, referencing Quranic verses related to light and shadow as sources of inspiration. The thesis classifies scholars' efforts into three phases: the first phase involves translating Greek heritage and correcting scientific errors; the second phase entails the standardization of optics and its theories by Alhazen; and the third phase consists of the rectification of the science of optics carried out by Muslim scholars. The thesis also addresses the West's adoption of Arabic optical science in the twelfth and thirteenth centuries, covering aspects such as translation, the nature of light, theories of visual perception, and underlying mathematics. The findings underscore the significant role of Islamic civilization in establishing the science of optics, laying the groundwork for modern studies.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B176-180.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdadSaI GdESdGejIs; (3Yde GdHUQjGJ s -- (3GdMVGQI GdESdGejIs -- (3YdeGA GdeSdejf s